A new kinetic model for biogas production from co-digestion by batch mode - D. Pham Van; M.G. Hoang; S.T. Pham Phu; T. Fujiwara (Global Journal of Environmental Science and Management)
Coming out from the growth kinetics, the Gompertz model has been developed and considered as the best one for simulating the biogas production from anaerobic digestion. However, the model has failed to describe the starting point of the process, and no-sense of lag phase constant has been pointed out. Thus, the goal of this study is to develop a new kinetic model of biogas production with meaningful constants that can alternate the Gompertz model. The kinetic constants of the model were determined by applying the least squares fitting method for experimental data. The experimental data were taken from running seven batch reactors of co-digestion of vegetable, sludge and horse manure under 37oC, pH of 6.7, and total solids of 2.5%. The result of the high coefficient of determination (0.9611-0.9906) demonstrated that the new biogas production kinetic model was feasible to simulate the biogas generation process. This finding has opened a new choice that can deal with simulation of the biogas production. Moreover, co-digestion of vegetable, horse manure, and sludge was also evaluated under strong attention. The biogas potential was in the range of 183-648 Nml/g-VS with the best carbon-to-nitrogen ratio of 16. Vegetable waste played a major role in producing the biogas yield while horse manure and sludge contributed to balancing nutrient of the digestion process. Also, the strong correlation between carbon-to-nitrogen ratio and kinetic constants confirmed that the carbon-to-nitrogen ratio was the key factor that influenced biogas generation.